Tissue specific age acceleration patterns in the sperm of oligozoospermic men - Stalker, Kelaney; Pollard, Chad; Aston, Kenneth; Jenkins, Tim (Frontiers in Reproductive Health, 2022)
To determine if disease can modify aging patterns in an affected tissue without altering the aging patterns of other tissues, blood and semen of individuals with oligozoospermia (n=10) were compared to the blood and semen of individuals with normozoospermia (n=24). DNA methylation data was obtained via Illumina’s 850K array. The Horvath and Jenkins age calculators were then utilized to predict the epigenetic age of blood and sperm. Using t-tests, it was found that sperm of oligozoospermic men (mean GLAD score of 0.078) were predicted to be significantly older than the sperm of normozoospermic men (mean GLAD score of -0.017), returning a p-value of 0.03. However, there was not a significant epigenetic age difference between the blood of those with oligozoospermia (mean GLAD equivalent score of -0.027) and normozoospermia (mean GLAD equivalent score of 0.048), producing a p-value of 0.20. These results lead to the conclusion that tissue specific aging is occurring in sperm of oligozoospermic individuals but not in unaffected somatic tissues (in this case, blood).